AS RELAÇÕES DE REPRESENTATIVIDADE DOS CONSELHEIROS MUNICIPAIS DE ASSISTÊNCIA SOCIAL DE PONTA GROSSA/PR - Rosa, Carla Bührer Salles (2011)
The participation of civil society in public spaces is ensured by the Federal Constitution of 1988 and both of them complement the opportunity of changes in the relations between State and society. The increasing participation proposed in the constitutional text expands the production spaces policy decisions, providing tools which enable greater social control over the state actions mainly in the elaboration of public policies with the participation of civil society groups in decision-making process which represents a breakthrough to the country democracy.The Organic Law of Social Assistance / LOAS which was created to regulate the constitutional text sets up the Councils of Social Welfare into three levels of management (Federal, State and Municipal) composed of an equal number of representatives of governmental and non-government segment to manage the policy in the area. The representative relationship between the representative and represented people in the Municipal Council of Social Service of Ponta Grossa / CMAS was the subject chosen for this study. The aim of this work was to understand how the counselor representative relations are established and how they are materialized in the CMAS discussions. The qualitative approach and dialectical method guided this research which methodologically was carried out by literature review, documentary research, observation and semi-structured interviews. The people who participated in this research were selected by cross-section and divided into two groups (counselors/representative and represented) during 2010 and 2011. The theoretical grounding made, gave the possibility for the analysis of the data contents collected from which emerged three categories: motivation and knowledge, materialization of the counselors representative in the Councils discussions and the relation of the councils with the represented segment. The research provided the identification of some features that mark the relations between the counselors/representative and represented in the Municipal Council of Social Service of Ponta Grossa such as the representative relations in CMAS are configured in a fragile link between the counselor representative and the represented basis but the government segment. The commitment of the representative councils with the represented and general interests are plain however there is a great weakness in the materialization of these interests because the difficulty of articulation between representatives and represented. In the representative relations of non-government segment were perceived interests of social entities and the users interests are little reflected by CMAS and when they arise is with no role of the own users.